2019
DOI: 10.1186/s12911-019-0866-0
|View full text |Cite
|
Sign up to set email alerts
|

Alerts for community pharmacist-provided medication therapy management: recommendations from a heuristic evaluation

Abstract: Background Medication therapy management (MTM) is a service, most commonly provided by pharmacists, intended to identify and resolve medication therapy problems (MTPs) to enhance patient care. MTM is typically documented by the community pharmacist in an MTM vendor’s web-based platform. These platforms often include integrated alerts to assist the pharmacist with assessing MTPs. In order to maximize the usability and usefulness of alerts to the end users (e.g., community pharmacists), MTM alert de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Conversely, we have found that the REDCap and Qualtrics programs offer features like data validation, force-functions and data repositories that decrease the likelihood of such data-collection mistakes. Overall, we found that the use of e-form/survey programs facilitated PPBR in a wide variety of methods, subjects and settings and are particularly helpful to conduct surveys and collect data [15,16,23,27].…”
Section: Electronic Form and Survey Softwarementioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, we have found that the REDCap and Qualtrics programs offer features like data validation, force-functions and data repositories that decrease the likelihood of such data-collection mistakes. Overall, we found that the use of e-form/survey programs facilitated PPBR in a wide variety of methods, subjects and settings and are particularly helpful to conduct surveys and collect data [15,16,23,27].…”
Section: Electronic Form and Survey Softwarementioning
confidence: 99%
“…The authors used several electronic tools to develop and deploy novel electronic data collection forms (i.e., e-forms/surveys) [4,[16][17][18][19][20][21][22][23]. In our experiences, we found that these 'e-form/survey' programs required little-to-no informatics training and were often accessible via desktop computers, tablets and other mobile devices alike.…”
Section: Electronic Form and Survey Softwarementioning
confidence: 99%
See 2 more Smart Citations
“…The designer participated in the qualitative analysis of the clinician interviews and the design workshop, and therefore had a deep understanding of the decision requirements and information needs. In addition, the designer's knowledge of clinical workflow and EHR use was informed by previous research and design projects including studies evaluating clinical decision support for medication therapy management, 43 designing a prototype for consult management for the Veteran's Health Administration, 44 and evaluating a modular decision support application for colorectal cancer screening. 45 Exploratory concepts started as sketches with pencil and paper.…”
Section: Prototype Designmentioning
confidence: 99%